Rasheedia n. nom. (Nematoda, Physalopteridae) for Bulbocephalus Rasheed, 1966 (a homonym of Bulbocephalus Watson, 1916), with description of Rasheedia heptacanthi n. sp. and R. novaecaledoniensis n. sp. from perciform fishes off New Caledonia - Moravec, František; Justine, Jean-Lou (Parasite (Paris, France), 2018)
The nematode genus Bulbocephalus Rasheed, 1966 (Nematoda, Physalopteridae) was found to be a homonym of Bulbocephalus Watson, 1916 (Apicomplexa) and, therefore, a new name, Rasheedia n. nom., is proposed to substitute it. Based on light and scanning electron microscope studies of specimens collected from the digestive tract of perciform fishes off New Caledonia, two new species of Rasheedia are described: R. heptacanthi n. sp. from the Cinnabar goatfish Parupeneus heptacanthus (Mullidae) (type host) and Dentex fourmanoiri (Sparidae), and R. novaecaledoniensis n. sp. from the Indian goatfish Parupeneus indicus (Mullidae). These new species are mainly characterized by the number of anterior protrusible oesophageal lobes (two in R. heptacanthi and four in R. novaecaledoniensis), structure of the oesophagus and the lengths of spicules. An amended diagnosis of Rasheedia and a key to species of this genus are provided. Three previously described congeneric species are transferred to Rasheedia as R. deblocki (Le-Van-Hoa, Pham-Ngoc-Khue & Nguyen-Thi-Lien, 1972) n. comb., R. inglisi (Rasheed, 1966) n. comb. and R. pseudupenei (Vassiliadès & Diaw, 1978) n. comb. Cestocephalus Rasheed, 1966 [genus inquirendum], including C. serratus Rasheed, 1966 and C. petterae (Le-Van-Hoa, Pham-Ngoc-Khue & Nguyen-Thi-Lien, 1972) n. comb., should be considered to be separate from Rasheedia. The names Pseudomazzia Bilqees, Ghazi & Haseeb, 2005 and P. macrolabiata Bilqees, Ghazi & Haseeb, 2005, established for a nematode somewhat resembling Rasheedia spp., should be considered nomina dubia. Rasheedia heptacanthi n. sp. and R. novaecaledoniensis n. sp. are the first representatives of the Physalopteridae recorded from fishes in New Caledonian waters.
Keywords: Animals; New Caledonia; Nematoda; Female; Nová Kaledonie; slezina; ženské pohlaví; Perciformes; nemoci ryb; Fish Diseases; gastrointestinální trakt; Aquatic Organisms; hlístice; Male; Spleen; vodní organismy; zvířata; mužské pohlaví; Gastrointestinal Tract